OVERVIEW: SANITATION CONDITIONS IN TERMINAL GAMALAMA, TERNATE CITY - muliyadi aras (Jurnal Vokasi Kesehatan, 2021)
Overview: Sanitation Conditions In Terminal Gamalama, Ternate City. The terminal as a public place, where human activity is so crowded also causes most of these people to spend time there. The research method is descriptive observational. The sample of this research is the total population, namely environmental health outside, environmental space and buildings, sanitation facilities, comfort and safety, and food health in the Ternate City gamalama terminal environment. Sampling uses a total sampling technique. The instrument used was the assessment sheet of the Ministry of Health's Republic of Indonesia Department of Health's Disease Prevention and Control. The stages of the study were data collection, then processed manually with stages of editing, tabulation, and then analyzed descriptively by comparing with existing regulations. The results showed that five of the components studied were none that met the requirements for environmental sanitation (75), sanitary space and buildings (58), sanitation facilities (103), comfort and safety (46), and food sanitation (32), and other facilities (14). Conclusion: In conclusion, sanitary facilities in terms of Gamalama are not eligible and can potentially interfere with health and comfort.